Respuesta :

[tex]x^2-6x+7=x^2-6x+9-2=(x-3)^2-2[/tex]

is a parabola with its vertex at [tex](3,-2)[/tex], which means the minimum value is [tex]-2[/tex].
[tex] x^{2} - 6 + 7 = 0[/tex]
a = 1; b = - 6, c = 7
Δ = b² - 4.a.c
Δ = (-6)² - 4.1.7
Δ = 36 - 28
Δ = 8

Calculate the minimum value:

[tex]Y_{v} = \frac{-\Delta}{4a} [/tex]

[tex]Y_{v} = \frac{-8}{4*1} [/tex]
[tex]Y_{v} = \frac{-8}{4} [/tex]
[tex]\boxed{Y_{v} = -2}[/tex]

Answer:
[tex]\boxed{\textcircled{ A } = -2}[/tex]

Follow the attachment (graphic):

Ver imagen dexteright02